High-Frequency Transformer-Link Inverter with Regenerative Snubber - Toh, L.S.; Salam, Zainal; Ramli, M.Z. (IEEE, 2006)
This work proposes a bidirectional high-frequency link High-frequency link inverters are now commonly used in inverter using center-tapped high-frequency transformer. The uninterruptible power supply and renewable energy source topology also incorporates a regenerative snubber to clamp the systems. In these applications, the types of loads connected to high voltage spikes due to the leakage inductance of the the inverter are rather uncertain. Nonlinear loads such as transformer. The closed-loop control method used is Deadbeat rectifier in computer systems could cause intense distortion in control, which provides fast response and low harmonic the output current and voltage waveform. It is desirable that the distortion, even under nonlinear loads. A lkVA prototype inverter be able to maintain a sinusoidal output voltage inverter is built and the workability of the system is waveform over all loading conditions. This can only be experimentally verified.